Anorectal malformations and the impact of HIV on surgical outcome - Gabler, Tarryn (My University, 2018)
Background: Anorectal malformations (ARMs) represent a significant surgical load in South African pediatric surgical centers. Surgical treatment of ARMs may be associated with postoperative complications owing to the nature of surgical procedures necessary in the neonatal and infantile period. Human Immunodeficiency Virus (HIV), and its effect on the immune response compound postoperative surgical complications. The impact of HIV exposure and its effect on the child’s immune status, independent of the child’s HIV status, has yet to be studied in the surgical population. Objectives: To assess the incidence of complications in our population of ARM patients and to explore whether these complications are increased in HIV exposed but serologically negative children compared to HIV not exposed children. Methods: This was a prospective study of all patients presenting with ARMs to the paediatric surgery units attached to the University of the Witwatersrand. Specifically, exposure to an HIV positive mother, patient’s HIV status, and presence of surgical complications were documented. This data was analysed for the period between August 2016 and September 2017. Results: A total of 50 participants were included, and none excluded. Nineteen participants (38%) were HIV exposed and none were HIV positive. Twenty-eight (56%) were male and 22 (44%) were females. Seventy-six operative procedures were performed with 27 operative complications. In the HIV exposed group 68% of participants experienced operative complications compared to 45% in the not exposed group (P = 0.1). In participants who had stoma formation 50% of the HIV exposed participants complicated, compared to 20% in the non-exposed group (p = 0.08). Conclusion: The incidence of postoperative infectious complications in HIV exposed patients is higher compared to HIV non-exposed patients. The incidence of postoperative complications in HIV non-exposed patients parallels that in the international literature, except in the posterior sagittal anorectoplasty groups. It remains critical to follow stringent perioperative protocols for infection prevention and aggressively treat any infection that arises, particularly in patients born to HIV positive mothers regardless of the patient’s HIV status.
A research report for submissible paper submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine in Paediatric Surgery November 2018